Function and association analysis of Cyclophilin A gene with resistance to Edwardsiella ictaluri in yellow catfish. (December 2020) - xiong, Yang; Zheng, Xiaozhen; Ke, Wensi; Gong, Gaorui; Wang, Yuhong; Dan, Cheng; Huang, Peipei; Wu, Jiankai; Guo, Wenjie; Mei, Jie
Abstract: Edwardsiella ictaluri ( E. ictaluri ) is one of the main bacterial pathogens in catfish which has caused serious economic loss to yellow catfish ( Pelteobagrus fulvidraco ) in China. In our previous work, we demonstrated that CypA was up-regulated at the early stage of E. ictaluri infection in yellow catfish and displayed strong chemotactic activity for leukocytes in vitro . However, the effect of CypA on E. ictaluri is unknown in vivo . Therefore, two homozygous transgenic zebrafish lines expressing yellow catfish CypA (TG- CypA -1 and TG- CypA -2) were generated. After challenged with E. ictaluri at a dose of 1.0 × 10 4  CFU per adult fish, both two transgenic lines exhibited a higher resistance to bacterial infection than the wildtype zebrafish. Herein, CypA gene in E. ictaluri -challenged yellow catfish was screened for presence of polymorphisms by sequencing and six single nucleotide polymorphisms (SNPs) were identified. SNP association analysis revealed that 528T/C SNP in the first intron was significantly different in disease-susceptible and -resistant groups, which was confirmed in two independent populations of yellow catfish. Moreover, the relative expression of CypA in the resistant group (CC genotype in 528T/C SNP) was significantly higher than that in the susceptible group (TT genotype in 528T/C SNP) in different immune organs of yellow catfish including spleen, head kidney, body kidney and liver. Our results reveal the potential function of CypA in host defense to bacterial infection and suggest the SNP marker in CypA gene associated with the resistance to E. ictaluri may facilitate the selective breeding of disease-resistant yellow catfish in the future. Highlights: Overexpression of yellow catfish CypA in zebrafish confers resistance to E. ictaluri . A SNP in yellow catfish CypA associates with disease resistance against E. ictaluri . CypA expression in resistant group is significantly higher than in susceptible group.